Prenatal exposure to long-term heat stress and stillbirth in Ghana: A within-space time-series analysis - Nyadanu, Sylvester D.; Tessema, Gizachew; Mullins, Ben; Kumi-Boateng, B.; Ofosu, A.A.; Pereira, Gavin (2023)
Introduction: Few studies examined the association between prenatal long-term ambient temperature exposure and stillbirth and fewer still from developing countries. Rather than ambient temperature, we used a human thermophysiological index, Universal Thermal Climate Index (UTCI) to investigate the role of long-term heat stress exposure on stillbirth in Ghana. Methods: District-level monthly UTCI was linked with 90,532 stillbirths of 5,961,328 births across all 260 local districts between 1st January 2012 and 31st December 2020. A within-space time-series design was applied with distributed lag nonlinear models and conditional quasi-Poisson regression. Results: The mean (28.5 ± 2.1 °C) and median UTCI (28.8 °C) indicated moderate heat stress. The Relative Risks (RRs) and 95% Confidence Intervals (CIs) for exposure to lower-moderate heat (1st to 25th percentiles of UTCI) and strong heat (99th percentile) stresses showed lower risks, relative to the median UTCI. The higher-moderate heat stress exposures (75th and 90th percentiles) showed greater risks which increased with the duration of heat stress exposures and were stronger in the 90th percentile. The risk ranged from 2% (RR = 1.02, 95% CI 0.99, 1.05) to 18% (RR = 1.18, 95% CI 1.02, 1.36) for the 90th percentile, relative to the median UTCI. Assuming causality, 19 (95% CI 3, 37) and 27 (95% CI 3, 54) excess stillbirths per 10,000 births were attributable to long-term exposure to the 90th percentile relative to median UTCI for the past six and nine months, respectively. Districts with low population density, low gross domestic product, and low air pollution which collectively defined rural districts were at higher risk as compared to those in the high level (urban districts). Discussion: Maternal exposure to long-term heat stress was associated with a greater risk of stillbirth. Climate change-resilient interventional measures to reduce maternal exposure to heat stress, particularly in rural areas may help lower the risk of stillbirth.